Development of Occlusion Concepts - Rapeepattana, Sirate; Theramontree, Angkana; Suntornlohanakul, Supanee (Thai Journal of Orthodontics, 2020)
Various occlusion concepts were developed from the past. The static and functional occlusion concepts play an important role in orthodontics such as problem identification, treatment goal determination, and treatment evaluation. Classification of static and functional occlusion as well as the different terms which explain the malocclusion characteristics were defined to fully describe the condition of malocclusion in each patient. The acceptable occlusion concept was developed from the indexes that used to identify the orthodontic treatment need. The purpose of these indexes was to screen the patient whom deserve the orthodontic treatment. The concept of index can be used as a guideline for dentists to define whether their patient’s malocclusion is acceptable or not.